THE DYNAMICS OF THE MICROBIOTA OF URINE IN PATIENTS WITH ACUTE OBSTRUCTIVE PYELONEPHRITIS IN PERIODS OF OBSERVATION. - Ju. L. Naboka; E. V. Mitusova; I. A. Gudima; P. P. Morgun; M. I. Kogan (Вестник урологии)
Abstract. Analysis of urine culture in 72 patients with acute obstructive pyelonephritis within 6 months. When hospitalization was performed urine culture before and after the elimination of the upper urinary tract obstruction (VMP). Over the next 5 days the patients received empirical antibiotic therapy until the results of the microbiological examination of urine, after which all patients were divided into two groups. 1 group of patients consisted of 38 people who received antibiotic therapy based on antibiotic susceptibility obschedokazannyh pathogens (E.coli, Proteus sp., Klebsiella sp., Enterococcus sp., Etc.), The 2 group of patients included 34 men treated with antibacterial treatment based antibiotic susceptibility of microorganisms isolated from urine. After the completion of antibiotic therapy, all patients underwent clinical and laboratory and bacteriological monitoring of urine through the 1,3 and 6 months follow-up.